Emotional Mental Imagery as Simulation of Reality: Fear and Beyond—A Tribute to Peter Lang. Issue 5 (September 2016) - Ji, Julie L.; Heyes, Stephanie Burnett; MacLeod, Colin; Holmes, Emily A.
Abstract: This article pays tribute to the seminal paper by Peter J. Lang (1977; this journal ), "Imagery in Therapy: Information Processing Analysis of Fear." We review research and clinical practice developments in the past five decades with reference to key insights from Lang's theory and experimental work on emotional mental imagery. First, we summarize and recontextualize Lang's bio-informational theory of emotional mental imagery (1977, 1979) within contemporary theoretical developments on the function of mental imagery. Second, Lang's proposal that mental imagery can evoke emotional responses is evaluated by reviewing empirical evidence that mental imagery has a powerful impact on negative as well as positive emotions at neurophysiological and subjective levels. Third, we review contemporary cognitive and behavioral therapeutic practices that use mental imagery, and consider points of extension and departure from Lang's original investigation of mental imagery in fear-extinction behavior change. Fourth, Lang's experimental work on emotional imagery is revisited in light of contemporary research on emotional psychopathology-linked individual differences in mental imagery. Finally, key insights from Lang's experiments on training emotional response during imagery are discussed in relation to how specific techniques may be harnessed to enhance adaptive emotional mental imagery training in future research.